Simultaneous determination and dietary risk assessment of clethodim and its metabolites in different fruits and vegetables. Issue 5 (4th May 2021) - Atzei, Alessandro; Pusceddu, Cristina; Caboni, Pierluigi; Corrias, Francesco
ABSTRACT: Clethodim is one of the most widely used herbicides in agriculture and, after field application, is metabolised to several metabolites. The potential toxicological negative effects of these compounds are poorly understood. Thus, recently, within the risk assessment framework, the European Food Safety Authority (EFSA) proposed to include the minor metabolites in the definition of clethodim residue. In this work, an easy to use and reliable UHPLC method coupled with a triple quadrupole MS/MS was developed and validated for the detection and quantification of the herbicide clethodim and related metabolites clethodim sulphone, clethodim sulphoxide, metabolites M17R and M18R in apple, grape, olive and rice. The five analytes were extracted by using a modified QuEChERS procedure, while the active ingredients were determined in multiple reaction monitoring (MRM) ion-switching mode. The proposed method showed calibration curve linearity with r 2 ≥ 0.990 for all active ingredients (a.is.) both in solvent and matrix extracts. Limits of quantitation (LOQ) of the five compounds ranged from 9.44 µg/kg for M17R in olive extract to 11.01 µg/kg for clethodim in apple extract. Recoveries values ranged from 86% to 119% at two concentration levels (LOQ and 10xLOQ), while the intraday and interday precisions of the method were both below 10% in all cases. The method was successfully used for the quantification of the five a.is. in different food matrices. Furthermore, chronic dietary risk was investigated using a hazard quotients (HQ) method based on European dietary habits. The chronic dietary exposure risk quotients ranged from 1.0 × 10 −5 (lower bound scenario) to 2.7 × 10 −4 (upper bound scenario) which were significantly lower than 1. Data obtained indicate that the dietary exposure risks were acceptable for clethodim and its major and minor metabolites applied in apple, table grape, rice and table olive.